Współczesne poglądy na patogenezę i leczenie masywnego krwotoku nadnaczyniówkowego - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
A massive suprachoroidal hemorrhage is a well-known, possibly serious complication of a variety of surgical procedures such as cataract extraction, penetrating keratoplasty, glaucoma-filtering operation, retinal detachment surgery and pars plana vitrectomy. It is defined as a hemorrhage, in the suprachoroidal space, of sufficient volume either to cause extrusion of intraocular contents outside of the eye or to force the inner retinal surfaces into apposition ("kissing"). Despite surgical interventions to drain the hemorrhage and establish normal anterior and posterior anatomic configurations to return of preoperative visual acuity is hard to prognosticate. This paper presents the current knowledge on the pathogenesis, risk factors, treatment of massive suprachoroidal hemorrhage.